fRFLP and fAFLP: Medium-Throughput Genotyping by Fluorescently Post-Labeling Restriction Digestion - Brian P. Lazzaro; Bonnielin K. Sceurman; Susan L. Carney; Andrew G. Clark (BioTechniques)
Genome-scale studies of population structure and high-resolution mapping of genetically complex traits both require techniques for accurately and efficiently genotyping large numbers of polymorphic sites in multiple individuals. Many high-throughput genotyping technologies require the purchase of expensive equipment or consumables and are therefore out of reach of some individual research laboratories. Conversely, less expensive technologies are often labor intensive so that the effort involved in typing large numbers of samples or polymorphic sites is prohibitive. Here we present a method of fluorescently post-labeling restriction digestion using standard dye-terminator sequencing chemistry so that RFLP and AFLP products can be visualized on an automated sequencer. This labeling method is efficient, inexpensive, easily multiplexed, and requires no unusual equipment or reagents, thus striking a balance between cost and throughput that should be appropriate for many research groups and core facilities.